(untitled) (Conferencea, 2024)
The relevance of the topic is due to the insufficient development of various forms of written tasks in modern teaching materials that form communicative written competence, the low results of students in writing, as well as the low development of foreign language communication in the virtual space. In addition to communicating in our native language in a variety of chats and forums on the Internet, we often encounter the need to write, read, and understand foreign speech. The purpose of this thesis is to study the possibilities of using creative writing tasks in the development of communicative written competence of students in learning foreign language.